SNACK BAR TINGGI SERAT DAN ANTIOKSIDAN BERBAHAN DASAR UBI JALAR UNGU DAN BERAS HITAM SEBAGAI ALTERNATIF SELINGAN PENDERITA DIABETES MELITUS - Aurelia, Lutvica Cery; Ma'rifah, Bahriyatul; Muhlishoh, Arwin (Jurnal Gizi dan Pangan Soedirman, 2023)
Type 2 diabetes mellitus is a metabolic disorder characterized by hyperglycemia due to decreased insulin secretion by pancreatic β-cells that requires dietary regulation to control blood glucose levels. Snack bars based on purple sweet potato flour and black rice flour which have high fiber and antioxidant content can be used as an alternative snack food for people with type 2 diabetes mellitus. The purpose of the study was to determine the nutritional content, dietary fiber content, antioxidants content and organoleptic properties of snack bars. This research was experimental with a completely randomized design (CRD) with three comparisons of formulation purple sweet potato flour: black rice flour and 3 repetitions. The results of the nutritional content were analyzed with the Anova test and continued with the Duncan test. While the organoleptic properties were analyzed by Kruskal Wallis test and continued by Man Whitney test. The selection of the selected formulation for snack bar products using the ratio (50%: 50%) from the results of the nutritional content test and organoleptic test. The results of the study show that F3 (70%:30%) snack bar is the selected formulation with nutritional content 100 g, namely energy 425 kcal, protein 13.80 g, fat 21.38 g, carbohydrates 44.23 g, dietary fiber 11.81 g and antioxidants 52.28% with less favorable organoleptic acceptance. The selected snack bar can be claimed as high dietary fiber and antioxidants food.